2016
DOI: 10.1097/igc.0000000000000786
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Institution Radical Surgery Results in Stage IB2/IIA2 (Bulky) Cervical Cancer

Abstract: Although adjuvant therapies are often resorted to, primary radical surgery is also a reasonable treatment option for stage IB2/IIA2 cervical cancer, especially in young premenopausal patients when preserving ovarian functions is desired.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…RS is aimed at removing the primary cervical lesion and surrounding tissue that may be involved, thereby reducing the risk of local recurrence and distant metastasis (20). In this study, 14.3% of patients relapsed, similar to the results of previous studies involving bulky early-stage CC treated with RS (10%-24.7%) (21)(22)(23). Keys et al (14) reported recurrence rates of 21% and 37% in patients with stage IB2 CC received with CCRT and RT alone, respectively, which were higher than the recurrence rates in this study.…”
Section: Discussionsupporting
confidence: 89%
“…RS is aimed at removing the primary cervical lesion and surrounding tissue that may be involved, thereby reducing the risk of local recurrence and distant metastasis (20). In this study, 14.3% of patients relapsed, similar to the results of previous studies involving bulky early-stage CC treated with RS (10%-24.7%) (21)(22)(23). Keys et al (14) reported recurrence rates of 21% and 37% in patients with stage IB2 CC received with CCRT and RT alone, respectively, which were higher than the recurrence rates in this study.…”
Section: Discussionsupporting
confidence: 89%
“…For stage IB2/IIA2 cervical cancer, concurrent chemoradiotherapy and radical hysterectomy + individualized postoperative adjuvant therapy were acceptable treatments, while the FIGO and NCCN guidelines indicated that because of the large diameter of IB2/IIA2 cervical cancer, the possibility of supplementing high and intermediate risk factors for radiotherapy after surgery was high, so platinum‐based concurrent chemoradiotherapy was a better choice for patients with IB2/IIA2 cervical cancer 1, 3 . In Europe, South Korea, China, and Japan, there have been reports of surgical treatment of patients with stage IB2/IIA2 cervical cancer, 9, 19–21 but they paid more attention to laparoscopic conditions such as bleeding volume, operation time, intraoperative postoperative complications, etc. There was no multicenter large‐scale report on tumor prognosis without preoperative adjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Definitive CCRT may lead to adverse effects such as ovarian function damage, cystitis, proctitis or hematological toxicity; however, surgery continues to be the major treatment for IB2 and IIA2 disease in some countries or regions suffered from limitation of the radiation equipment and technology. The tumors > 4 cm increase the difficulty of the operation, and thus, the patients with IB2 and IIA2 disease need a comprehensive therapeutic strategy [ 6 ].…”
Section: Introductionmentioning
confidence: 99%